Borilni športi in borilne veščine v Sloveniji - Šimenko, Jožef (Šport (Ljubljana), 2014)
Martial Arts and Sports accompany us through our entire existence. They are an indispensable means of physical exercise, self-defense and various defense systems, which have evolved. The purpose of this article is to briefly present the history of martial arts and to explain the difference between the meaning of words martial arts and combat sports. In the following is an overview of the possibilities and training martial arts in Slovenia and overview of combat sports inside of the Slovenian Olympic Committee.Martial Arts and Sports accompany us through our entire existence. They are an indispensable means of physical exercise, self-defense and various defense systems, which have evolved. The purpose of this article is to briefly present the history of martial arts and to explain the difference between the meaning of words martial arts and combat sports. In the following is an overview of the possibilities and training martial arts in Slovenia and overview of combat sports inside of the Slovenian Olympic Committee.
Keywords: borilne veščine; borilni športi; combat sports; history; martial arts; Slovenia; Slovenija; sport; šport; športna dejavnost; training; trening; zgodovina; zveze borilnih športov